A Mobile-Assisted Working Model for Supporting Daily Family Life: A Pilot Study. (April 2015) - Rönkä, Anna; Malinen, Kaisa; Jokinen, Kimmo; Häkkinen, Sanna
Despite rapid technological development, very few new technology-assisted tools have been developed specifically for use in family services. This article describes a new, mobile-assisted working model designed to enhance the quality of daily family life. The model has its origins in the existing research on daily family life and on the diary method, which has been widely used in data collection in family research. The model provides support for the daily life of client families in the intervals between meetings with family counselors via the use of text messages. The pilot study explored family members' and family counselors' experiences of using the model. Data on 26 parents and four children participating in the new mobile-based service were collected via feedback text messages and web questionnaires. The research findings are also based on interviews with family counselors ( n = 6). Although clients' experiences of the model varied widely, the results show that, in general, it was regarded as effective in invoking reflection, keeping the goals of family counseling in mind and implementing family practices at home. On the basis of the experiences of the family counselors, the mobile-based working model offers a new, systematic, and structured tool for use in working with families and monitoring processes in families.